Effectiveness of Community Pharmacy Diabetes and Hypertension Care Program: An Unexplored Opportunity for Community Pharmacists in Pakistan - Madeeha Malik (Frontiers in Pharmacology, 2022)
Background: The effective management of patients diagnosed with both Diabetes as well as Hypertension is linked with administration of efficacious pharmacological therapy as well as improvement in adherence through counseling and other strategies. Being a part of primary healthcare team, community pharmacists can effectively provide patient care for chronic disease management. The objective of the study was to evaluate the impact of pharmacist counseling on blood pressure and blood glucose control among patients having both hypertension and diabetes attending community pharmacies in Pakistan.Method: A randomized, controlled, single-blind, pre-post-intervention study design was used. The respondents included patients diagnosed with diabetes mellitus (Type I or II) and hypertension visiting community pharmacies to purchase their regular medicine. A simple random sampling technique using the lottery method was used to select community pharmacies in groups A (intervention, n = 4) and group B (control, n = 4). The total number of patients was 40 in each group, while estimating a dropout rate of 25%. The patients in the intervention group received special counseling. Blood pressure and blood glucose were checked after every 15 days for 6 months. Prevalidated tools such as the hypertension knowledge level scale, the diabetes knowledge questionnaire 24, and a brief medication questionnaire was used. Data were coded and analyzed using SPSS 21. Wilcoxon test (p < 0.05) was used to compare pre-post intervention knowledge regarding the disease, while the Mann-Whitney test (p < 0.05) was used to find differences in medication adherence among control and intervention groups.Results: A significant improvement in mean knowledge scores of patients with diabetes (16.02 ±2.93 vs. 19.97 ±2.66) and hypertension (15.60 ±3.33 vs. 18.35 ±2.31) in the intervention group receiving counseling for 6 months than control group (p < 0.05) was noted. Furthermore, the fasting blood glucose levels (8.25 ±1.45) and systolic BP (130.10 ±6.89) were significantly controlled after 6 months in the intervention group.Conclusion: The current study results concluded that community pharmacists’ counselling has a positive impact on blood glucose and blood pressure management among patients suffering with both diabetes and hypertension.